The Semiotics of The Title In The Poetry Collection (I Do Not Sing) By Mahdi Al-Nahiri - Hami تغريد خليل; Al-Battat رائد حميد (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The modern poetic text in its semiotic symbols and interpretive connotations is full of mechanisms of textual openness, and at the forefront of these mechanisms is the title as a semiotic interpretive sign that creates a symbolic question answered by the poetic text first, and the uniqueness of the title with an intensive linguistic economy that refers to intentional relations to the world, the text and the recipient secondly, which pushes the search for the interpretation of ideas and connotations that are subject to the endless series of reading processes, and the influential interaction between the recipient self and the structure of the poetic text, hence the study seeks to research the semiotics of The title in the poetry collection (I do not sing) by Mahdi Al-Nahiri through an interpretive semiotic reading of the symbolism of the title and its manifestations in the poetic text.